Secession and the Sovereignty Game : Strategy and Tactics for Aspiring Nations - Griffiths, Ryan D. (Book collections on Project MUSE., 2021)
"The author provides a theoretical and empirical analysis of the strategies and tactics of secessionist movements in the international system. More than sixty contemporary secessionist movements are examined. Fieldwork was conducted in Catalonia, the Murrawarri Republic, West Papua, Bougainville, New Caledonia, and Northern Cyprus"--